Children as Cosmopolitan Citizens: Reproducing and Challenging Cultural Hegemony - Supa, Markéta; Nečas, Vlastimil; Rosenfeldová, Jana; Nainova, Victoria (International Journal of Multicultural Education, 2021)
The article argues that, although digital and social media provide space and means for children's cosmopolitan citizenship, the tendency to reproduce cultural and ethnic stereotypes and prejudice prevalent in mainstream media can limit their capability and willingness to act and think as such. Drawing upon qualitative participatory research conducted with more than seventy children living in the Czech Republic, the article explores how children's media practice had a tendency to reproduce cultural hegemony. The paper ultimately argues that multicultural education and media education can together support children in reflecting on and challenging cultural hegemony, while at the same time potentially contribute to their transnational participation and cooperation with the use of digital and social media.